Delavnica za učitelje s praktičnim delom v šolski knjižnici - Antolič, Sonja (Šolska knjižnica, 2012)
The paper shows an example of presentation of library use to teachers. The main goal of this workshop was to present the possibilities which a library and its resources offer for solving an information problem. The teachers, in the roles of pupils, came to know the problems with which the pupils are faced when preparing various written assignments. Experiential learning - awareness of a problem - was a means of making teachers think about giving instructions regarding written assignments. Different instructions would facilitate the solving of an information problem which is a difficult task for the pupils thus requiring systematic introduction in class.
Keywords: informacijski viri; informacijsko opismenjevanje; šolske knjižnice; učitelji